Hematological parameters and protein metabolism in the blood of pregnant rats under the effect of vanadium citrate - H. V. Klymets; R. Y. Iskra; O. Z. Svarchevska (Regulatory Mechanisms in Biosystems, 2021)
Dose-dependent changes in protein metabolism in the blood and hematological parameters of pregnant rats under the effect of vanadium citrate are presented in the article. The animals were divided into five groups: group I – non-pregnant females, II – pregnant females consuming pure water without additives, III, IV, V – females which during the mating and pregnancy period received the solution of vanadium citrate at concentrations of 0.03, 0.125 and 0.50 μg V/mL water. The research findings show that in pregnant animals of group II, the level of urea and alkaline phosphatase activity increased, meanwhile aspartate aminotransferase activity decreased, as compared to the non-pregnant females of group І. The levels of total protein and albumin decreased; however, the content of β-globulins increased in the pregnant animals of group II, as compared with that in group I. Also, in the rats of group II, there was a decrease in hemolysis time, total content of erythrocytes and hemoglobin, the content of old and mature erythrocytes, while the content of young erythrocytes increased, as compared to group I. The platelet content and thrombocrit in rats of group II increased in comparison with group I. The content of leukocytes and lymphocytes in pregnant animals of group II decreased, while the content of granulocytes increased, in contrast to non-pregnant rats. Under the effect of vanadium citrate at concentrations of 0.03–0.50 μg V/mL, there was a significant increase in the maximum number of prohemolized erythrocytes, the time of maximum hemolysis was delayed by 0.4–0.6 min, as compared with the pregnant rats of group II. This did not affect the time of total hemolysis in rats of groups III and V, as compared with the pregnant animals in group II. Under the effect of vanadium citrate, an increase in the content of young erythrocytes was observed, as compared with group II. The hemoglobin content decreased at the concentration of 0.125 μg V/mL, while at the concentration of 0.50 μg V/mL it increased, as compared to the pregnant animals of group II. Also, under the effect of vanadium citrate there was a decrease in the mean hemoglobin concentration in the erythrocyte. In pregnant animals fed with vanadium citrate solutions, the platelet content and thrombocrit, the relative width of platelet distribution by volume decreased, as compared with the pregnant rats of group II. The content of leukocytes, lymphocytes and granulocytes under the effect of vanadium citrate increased, as compared with the pregnant animals in group II. Under the effect of vanadium citrate at the concentration of 0.03 μg V/mL, the level of albumin, creatinine and aspartate aminotransferase activity increased in blood plasma in comparison with group II. Meanwhile, at the concentration of 0.125 μg V/mL, the relative content of γ-globulins and aspartate aminotransferase activity increased, alkaline phosphatase activity and urea level decreased in comparison with group II. However at the concentration of 0.50 μg V/mL, the relative α- and γ-globulins content and aspartate aminotransferase activity increased, at the same time, the relative β-globulins content and urea level decreased in comparison with group II. Therefore, vanadium citrate normalizes the indicators of protein metabolism during pregnancy, thus it can be considered as a potential dietary drug for the pregnant.